EXPLORING EFL STUDENTS’ EXPERIENCES ON ONLINE-BASED WRITING PORTFOLIO - Abdul Halim; Khusnul Khatimah; Dzul Rachman; Azhar Aziz Lubis; Sunarti Sunarti; Rani Herning Puspita (Universitas Muhammadiyah Kalimantan Timur, 2019)
The aim of this study was to explore students’ experience towards online-based writing portfolio. As the use of information technology evolved, the penetration of online lifestyle into youths’ life has inevitably come deeper. In order to get the students engaged with their lesson, it was decided to make use of some online platforms for the students to work with their tasks in writing course. Utilizing qualitative method the study involved 30 students of English Department in Universitas Muhammadiyah Kalimantan Timur. The instrument for data collection was a questionnaire with open-ended questions. The results showed that in general students were motivated to use the platforms as learning media for writing. They found it easy to write their essay assignments with these facilities since it could develop creativity.